Characterizing trends in fruit and vegetable intake in the USA by self-report and by supply-and-disappearance data: 2001–2014. Issue 17 (20th September 2017) - Conrad, Zach; Chui, Kenneth; Jahns, Lisa; Peters, Christian J; Griffin, Timothy S
Abstract: Objective: To examine the comparability of fruit and vegetable (F&V) intake data in the USA from 2001 to 2014 between data acquired from two national data collection programmes. Design: Cross-sectional analysis. Linear regression models estimated trends in daily per capita intake of total F&V. Pooled differences in intake of individual F&V ( n 109) were examined by processing form (fresh, frozen, canned, dried and juice). Setting: What We Eat in America (WWEIA, 2001–2014) and Loss-Adjusted Food Availability data series (LAFA, 2001–2014). Results: No temporal trends were observed in daily per capita intake of total F&V from 2001 to 2014 using WWEIA and LAFA. Modest differences between WWEIA and LAFA were observed in mean pooled intake of most individual F&V. Conclusions: WWEIA and LAFA produced similar estimates of F&V intake. However, WWEIA may be best suited for monitoring intake at the national level because it allows for the identification of individual F&V in foods with multiple ingredients, and it is structured for sub-population analysis and covariate control. LAFA does retain advantages for other research protocols, specifically by providing the only nationally representative estimates of food losses at various points in the food system, which makes it useful for examining the adequacy of the food supply at the agricultural, retail and consumer levels.